Two-lane blacktop [videorecording (DVD)] - Taylor, James, 1948-; Oates, Warren, 1928-1982; Bird, Laurie, -1979 (Criterion collection, 2007)
A car-obsessed Driver and Mechanic aimlessly head East from L.A. in a souped-up 1955 Chevy, drag racing for money and thrills. Drifting across the Southwest, they keep being buzzed by a Pontiac GTO. They are joined by The Girl after she climbs into their car while the two are eating in a diner. Later at a gas station, the three meet "GTO" and challenge him to a cross-country race to Washington, D.C. for "pink slips," where the winner will get the loser's car. Along the way, however, they keep stopping to help each other, and winning seems far from their thoughts. The road is itself a place to live, is home, not just a way to move.